Echoing Arabic Language: Applying the Advantages of Internet-Based Arabic Language Instruction in Digital Era - Nisa, Sayyidah Ilman; Jatmika, Sidik (Universitas Muhammadiyah Yogyakarta, 2023)
Arabic is one of the world languages that has complex value. It has been spoken by previous Islamic scientists. As time goes by, the digital era brings changes to the learning process of Arabic. With the sophistication of technology, the internet has an important role in the process of learning Arabic in the digital era. The method used in this study using is the Quantitative Approach and a Descriptive Approach Through Literature Study. Supported by conducting a survey of respondents related to the urgency of learning Arabic in the digital age. The results of this finding that the concept of learning Arabic based on internet has a very important value. This can be viewed from the values of contextual value excellence with the learning of e-learning as in the cup of motivation, orientation, material, strategy, and media. Supported by teacher participation in understanding good strategies and learning methods that can be taught to students. So this article aims to find out the value of the excellence of the internet in the Arabic learning process in the digital age.